SUNAN KALIJAGA’S HERITAGE IN JAVANESE CULTURE IN RELATION TO THE PREVENTION OF CORRUPTION - Arif Julianto (Asia Pacific Fraud Journal, 2018)
Javanese tribe has been known to have a high civilization. This is evidenced by the concept of a very philosophical life. In the 14th century, Sunan Kalijaga already taught the concept of fraud prevention and detection. In the 19th century, the American Institute of Certified Public Accounts (AICPA) drafted the guiding concept to prevent and detect the existence of fraud that is not much different from the concept of Sunan Kalijaga. It proves that the philosophy of Javanese culture is quite advanced, especially related to the prevention of fraud.